2008
DOI: 10.1016/j.jacc.2008.04.068
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Caloric Restriction in Obese Patients With Type 2 Diabetes Mellitus Decreases Myocardial Triglyceride Content and Improves Myocardial Function

Abstract: Prolonged caloric restriction in obese T2DM patients decreases BMI and improves glucoregulation associated with decreased myocardial TG content and improved diastolic heart function. Therefore, myocardial TG stores in obese patients with T2DM are flexible and amendable to therapeutic intervention by caloric restriction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
159
5
5

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 231 publications
(179 citation statements)
references
References 40 publications
10
159
5
5
Order By: Relevance
“…Hammer and colleagues reported that a shortterm very low-calorie diet increases myocardial triglyceride content and is associated with a decrease in left ventricular diastolic function in patients with well-controlled type 2 diabetes [76] . Furthermore prolonged caloric restriction improves 1114 www.nature.com/aps Han X et al Acta Pharmacologica Sinica npg glucoregulation associated with decreased myocardial triglyceride content and favorable effects on blood pressure and myocardial function in insulin-treated obese patients with type 2 diabetes [77] . These data prove that myocardial triglyceride stores in obese patients with type 2 diabetes are flexible and amendable to therapeutic intervention by caloric restriction.…”
Section: Diabetes Mellitus and Metabolic Syndromementioning
confidence: 99%
“…Hammer and colleagues reported that a shortterm very low-calorie diet increases myocardial triglyceride content and is associated with a decrease in left ventricular diastolic function in patients with well-controlled type 2 diabetes [76] . Furthermore prolonged caloric restriction improves 1114 www.nature.com/aps Han X et al Acta Pharmacologica Sinica npg glucoregulation associated with decreased myocardial triglyceride content and favorable effects on blood pressure and myocardial function in insulin-treated obese patients with type 2 diabetes [77] . These data prove that myocardial triglyceride stores in obese patients with type 2 diabetes are flexible and amendable to therapeutic intervention by caloric restriction.…”
Section: Diabetes Mellitus and Metabolic Syndromementioning
confidence: 99%
“…This is a challenging approach as the heart is always in motion owing to contraction and breathing, and because previous studies have already shown that myocardial TG stores may change rapidly depending on nutritional conditions. [27][28][29][30] MRI was recently used in mildly obese patients to suggest that the increase in MTGC could be associated with cardiac dysfunction. [31][32][33] To date, no study has addressed the relationship between EFV and MTGC in morbidly obese patients, a population with an abundance of fat in different depots and a high risk of cardiac failure, 34 because of the relatively small diameter of the MRI magnet bore.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the quantification of cardiac steatosis remains challenging, essentially because the acquisition of the spectra needs a double trigger (ECG and respiratory). It has also been shown that myocardial triglycerides decrease after energy restriction in obese type 2 diabetes patients 33,34 and that this decrease in myocardial triglycerides is associated with better cardiac function.…”
Section: Fat Deposits and Fat Imagingmentioning
confidence: 97%